‘Axis of evil or access to diesel?: spaces of new imperialism and the Iraq war’ - Bieler, Andreas; Morton, Adam David (Brill, 2015)
The invasion of Iraq in 2003 was waged by the so-called ‘Coalition of the Willing’. This paper will examine how the war was a space in the ongoing geographical extension of global capitalism linked to U.S. foreign policy. Was it simply the decision by a unitary, hegemonic actor in the inter-state system overriding concerns by other states? Was it an imperialist move to secure the ‘global oil spigot’? Alternatively, did the use of military force reflect the interests and emergence of a transnational state apparatus? In this paper, we argue that the U.S. needs to be conceptualised as a specific form of state, within which and through which national and transnational capital operate to establish the interests of a national fraction of an Atlantic ruling class. It is these processes of class struggle and their relation to wider struggles over spaces of imperialism, which need to be at the centre of analysis.